Disembodiment of Symbols and Presence of the Body: An Embodied Logic of Taijiquan’s Cultural Transmission in the Digital Era - Zhang, Shaojie (The Journal of the International Society of Chinese Health Practices, 2025)
Abstract: Research Purpose: As a representative intangible cultural heritage of the Chinese nation, the transmission of Taijiquan is fundamentally an embodied practice based on "bodily presence," emphasizing the conveyance of tacit knowledge—such as the inner experiences of "Qi," "Jin," and "Shen"—through physical comprehension. However, with the proliferation of digital media, its inherent characteristic of "disembodiment" creates a profound paradox with Taijiquan’s requirement for "bodily presence." Current digital dissemination often leads to a "separation of form and intent" in Taijiquan, a superficialization of its cultural connotations, and even its reduction to a symbolized and spectacularized cultural token. This paper aims to address this practical dilemma by exploring how digital technology can transition from dissolving physicality to reconstructing it, thereby establishing a new paradigm of "technology-mediated re-embodiment." The goal is to promote the deep-level and sustainable transmission of Taijiquan in the digital age and provide theoretical reference for the digital survival of other intangible cultural heritage practices. Research Methods: This study adopts a research approach that combines interdisciplinary theoretical construction with typical case analysis. On the theoretical level, it integrates perspectives from communication studies, phenomenology, sociology, and cultural studies to construct a three-dimensional integrative analytical framework encompassing "semantics, experience, and society." Specific theoretical tools include: 1) Media theory, to analyze the disembodied nature of digital symbols; 2) Embodied cognition theory, to explain the foundational role of the body in cognition and communication; 3) Cultural memetics, used to structurally decode the cultural system of Taijiquan; and 4) Spatial and social interaction theory, to explore the construction of digital communities and the mechanism of value internalization. On the practical level, the study selects typical cases such as the "Kung Fu Metaverse," AR Taijiquan teaching applications, and international Taijiquan digital communities, conducting in-depth analyses of their technological logic, user experience, and community practices to verify the validity and applicability of the theoretical model. Research Results: The study proposes and systematically elaborates a three-dimensional logical pathway for achieving the "re-embodiment" of Taijiquan’s digital transmission: mantic Dimension: The computational translation of cultural memes. Taijiquan is viewed as a composite system consisting of three major meme clusters: "technique, language, and ethics." Through technologies like motion capture, biomechanical analysis, and natural language processing, it undergoes parametric modeling and semantic network construction, forming a "dynamic knowledge graph" and a "digital gene bank" recognizable and processable by computers. This lays a structured, computable semantic foundation for embodied communication. Experiential Dimension: The phenomenological empowerment through immersive technology. Utilizing technologies like VR/AR and somatosensory interaction, a "phenomenological field" is constructed, transforming users from passive viewers into active experiencers. The system provides real-time correction of user movements through multi-sensory feedback (visual, auditory, tactile), simulating the bodily feedback mechanism of the traditional master-apprentice system. This transforms abstract principles into "quasi-experiences" perceivable by the body, thereby enabling the technologically mediated transmission of tacit knowledge. Social Dimension: The spatial re-embedding within digital communities. By constructing cross-spatiotemporal online Taijiquan communities (e.g., virtual dojos, online group practice, digital commemorative rituals), individualized embodied experiences are aggregated into "communities of interest" characterized by identity and cohesion. These digital rituals and social interactions not only reshape traditional master-disciple relationships but also facilitate the internalization of ethical values and the formation of collective identity, culminating in the sublimation of cultural transmission from individual experience to social consensus. Research Conclusion: This study concludes that the effective transmission of Taijiquan in the digital age is not merely a simple digital replication of traditional models but rather a profound paradigm reconstruction. Its core lies in consciously using technology to transcend the inherent "disembodied" limitations of digital media, achieving a "technology-mediated re-embodiment." The proposed "semantic-experiential-social" three-dimensional logic systematically reveals a complete transmission pathway from content structuring to immersive experience, and further to value socialization. This framework is applicable not only to Taijiquan but also provides theoretical support for the digital dissemination of other intangible cultural heritage practices reliant on bodily practice (such as traditional opera, martial arts, and crafts). Future cultural digitization strategies should shift from a "resource preservation"-oriented database mindset to an ecosystem thinking focused on "experience generation" and "community co-construction." Simultaneously, it is necessary to remain vigilant about potential new risks of alienation brought by technology and to further explore the complementary relationship between virtual presence and physical presence, aiming to achieve the genuine "living transmission" of traditional culture in the digital era.